2015
DOI: 10.1001/jamaophthalmol.2015.51
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Intraocular Pressure Increase in Patients With Uveitis Treated With the Fluocinolone Acetonide Implant

Abstract: IMPORTANCE Elevated intraocular pressure (IOP) is a well-known adverse event associated with the fluocinolone acetonide implant (FAI), but no data are available regarding factors associated with increased risk of IOP elevation in patients treated with the FAI.OBJECTIVE To report risk factors that may predispose patients to elevated IOP after treatment with the FAI. DESIGN, SETTING, AND PARTICIPANTS Data from 3 multicenter, 3-year, prospective, randomized, phase 2b/3 clinical trials evaluating the safety and ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 22 publications
0
7
1
Order By: Relevance
“…They found that children younger than 6 years old may be great steroid responders (16). Studies done in the adults have mentioned older age, age under fty or thirty as risk factors for IOP elevation (17)(18)(19). In our study, the HR for age wasn't signi cant.…”
Section: Discussioncontrasting
confidence: 62%
“…They found that children younger than 6 years old may be great steroid responders (16). Studies done in the adults have mentioned older age, age under fty or thirty as risk factors for IOP elevation (17)(18)(19). In our study, the HR for age wasn't signi cant.…”
Section: Discussioncontrasting
confidence: 62%
“…This implant provides substantial visual benefit by delivering the drug to the posterior eye tissue for up to 3 years (8). But unfortunately, patients receiving the fluocinolone acetonide implant are at higher risk of developing an increase in their intraocular pressure which is a major potential complication for this dosage form (9), in addition to the patient incompliance which may be encountered with the implant administration.…”
Section: Introductionmentioning
confidence: 99%
“…Young age at implantation has been associated with IOP rise after the FAI implantation (Parekh et al. ). The success rate of the four IOP‐lowering surgeries in our study was high: no reoperations were performed and only one patient needed antiglaucomatous medication by the last follow‐up.…”
Section: Discussionmentioning
confidence: 99%